IMPLEMENTASI METODE BIT MATCHING UNTUK KEAMANAN PESAN TEKS MENGGUNAKAN VISUAL BASIC. NET - Reno Supardi ((JurTI) Jurnal Teknologi Informasi, 2017)
Abstrack - Information and communication technology has developed rapidly, giving a great influence to human life. The development of network and internet technology allows everyone to exchange data, information, or messages to others without limitation of distance and time. Security and confidentiality are important aspects needed in the process of exchanging messages / information. The author uses steganography with the Bit Matching method that will hide information in the form of text into other digital image media. After being analyzed and implemented using the Visual Basic 2010 programming language, it was found that the text that was inserted into the image still looked normal so that it did not raise suspicion for those who saw it. The size of the capacity of a digital image affects how many characters a text message can be hidden. The greater the number of text message characters that will be hidden, the greater the size of the digital image. It is expected that this application of steganography can be useful in the fields of education and science especially in concealing text messages and can be continued for future research. Keywords - Digital Image, Bit Matching, Visual Basic 2010